2020
DOI: 10.1186/s12917-020-02423-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary Mannan-oligosaccharide and β-Glucan supplementation on growth, histopathology, E-coli colonization and hepatic transcripts of TNF-α and NF- ϰB of broiler challenged with E. coli O78

Abstract: Background: Using probiotics have become popular. They are considered an alternative to Antibiotic Growth Promoters (AGP). Probiotics are supplemented into animal feed for improving growth performance along with preventing and controlling enteric pathogens. The aim of this work was to study the impact of dietary supplementation of Mannan-oligosaccharide and β-Glucan (Agrimos®) on broiler challenged with Escherichia coli O 78 (E. coli O 78-marked with an antibiotic (320 μg ciprofloxacin/ml broth) on growth perf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…As shown in our study, the addition of Saccharomyces cell wall/Nanocurcumin alone/in combination to the aflatoxin-contaminated diet alleviated the toxic effects of aflatoxin B1 on the hepatic function in broilers fed on for 35 days, where the serum total protein, albumin, and globulin concentrations were increased. These results are compatible with previous studies [ 63 65 ]. On the other hand, Li et al [ 66 ] explained that YCW incorporation did not affect the same biochemical indices, including total protein, albumin, and globulin.…”
Section: Discussionsupporting
confidence: 94%
“…As shown in our study, the addition of Saccharomyces cell wall/Nanocurcumin alone/in combination to the aflatoxin-contaminated diet alleviated the toxic effects of aflatoxin B1 on the hepatic function in broilers fed on for 35 days, where the serum total protein, albumin, and globulin concentrations were increased. These results are compatible with previous studies [ 63 65 ]. On the other hand, Li et al [ 66 ] explained that YCW incorporation did not affect the same biochemical indices, including total protein, albumin, and globulin.…”
Section: Discussionsupporting
confidence: 94%
“…In general, pathogenic E. coli -infection is associated with reduced feed intake and intestinal mucosal damage ( Mellata, 2013 ). In the present study, we found that E. coli O78 infection resulted in increased immune-related organs indexes (spleen index and thymus index) and impaired gut mucosal morphology of broilers, indicating that animal model of E. coli infection has been successfully established ( Fadl et al, 2020 ). Previous studies have demonstrated that functional amino acids, like Gln and tryptophan ( Trp ), exerted positive role in anti-inflammation and cell proliferation, which might account for the amelioration of immune organic compensatory hypertrophy and the intestinal mucosal impairment of E. coli O78-induced broilers ( Maiorka et al, 2016 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 61%
“…The probiotic dietary inclusion decreased the serum activities of ALT, AST, and ALP in the laying hen ( 62 ). Other findings reported that probiotics dietary supplementation without heat stress does not affect the serum activities of AST and ALT ( 66 ). These results have been confirmed by the results of MDA and antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 98%